2007
DOI: 10.17221/2357-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weaning system on lamb growth and commercial milk production of Awassi dairy sheep

Abstract: To determine the effect of weaning system on Awassi sheep milk production and lamb growth, 68 Awassi ewes and their lambs (<i>n</i> = 104) were assigned to one of the following treatment groups a) after 3 days from birth (MIX), ewes were separated from their lambs during the evening for 15 h and milked once daily in the morning, and their lambs were allowed to suckle for 9 h during the day or b) ewes were not milked and suckled by their lambs (DY60) during the first 60 days of lactation. Ewes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
12
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 17 publications
8
12
0
5
Order By: Relevance
“…The results showed that the birth weight was higher in males compared to females and in single-born lambs compared to twins. These results were in consistent with those reported by Dikmen et al, (2007). Singles and males generally had higher birth weights than twin births and females.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that the birth weight was higher in males compared to females and in single-born lambs compared to twins. These results were in consistent with those reported by Dikmen et al, (2007). Singles and males generally had higher birth weights than twin births and females.…”
Section: Resultssupporting
confidence: 93%
“…The WW was higher in males compared to females and in single-born lambs compared to twins. Similar finding was obtained by Dikmen et al, (2007), Al-Salman (2009) and Üstüner and Oğan (2013).…”
Section: Resultssupporting
confidence: 89%
“…Results showed that the birth weight was higher in males compared to females and in single-born lambs compared to twins. These results were in consistent with those reported by Dikmen et al (2007). Singles and males generally had higher birth weights than twin births and females.…”
Section: Resultssupporting
confidence: 93%
“…Highly productive ewes are able to produce more milk than suckling lambs need for their growth Thomas et al, 2014). However, rearing systems with lambs enabled to suckle ewes either exclusively or partially prior to exclusive machine milking occur occasionally (Marnet and McKusick, 2001); in spite of fact that about 25 to 30% proportion of milk yield is produced during first 30 to 60 days of lactation (Folman et al, 1966;Dikmen et al, 2007). It was indicated that lamb rearing systems with ewes milked only after lambs are weaned decrease milk yield and reduce flock profitability (Gargouri et al, 1993;McKusick et al, 2001).…”
Section: Introductionmentioning
confidence: 99%